2019
DOI: 10.2174/1381612825666190326143814
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Corticosteroids for Fetal Lung Maturity - Too Much of a Good Thing?

Abstract: Background: Between 5-15% of babies are born prematurely worldwide, with preterm birth defined as delivery before 37 completed weeks of pregnancy (term is at 40 weeks of gestation). Women at risk of preterm birth receive antenatal corticosteroids as part of standard care to accelerate fetal lung maturation and thus improve neonatal outcomes in the event of delivery. As a consequence of this treatment, the entire fetal organ system is exposed to the administered corticosteroids. The implications of this exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 102 publications
0
10
0
4
Order By: Relevance
“…Additionally, some of these hormones are exogenously administered during pregnancy, but without consideration of their normal diurnal variation. For example, women at risk of preterm birth receive antenatal corticosteroids as part of standard care to improve neonatal outcomes (90). Knowing the appropriate daily profile and roles of glucocorticoids (e.g., in entraining the fetus) could inform the best times of day and doses for steroid treatment to promote fetal development and circadian entrainment.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some of these hormones are exogenously administered during pregnancy, but without consideration of their normal diurnal variation. For example, women at risk of preterm birth receive antenatal corticosteroids as part of standard care to improve neonatal outcomes (90). Knowing the appropriate daily profile and roles of glucocorticoids (e.g., in entraining the fetus) could inform the best times of day and doses for steroid treatment to promote fetal development and circadian entrainment.…”
Section: Resultsmentioning
confidence: 99%
“…More than 50% of pregnant women who received prenatal corticosteroids continue their pregnancy beyond day 7 from maturity or go to term [ 10 ]. It is also estimated that 15% of pregnant women who received prenatal corticosteroids finish their pregnancy before 48 h from the start of regimen, sometimes without having received the two doses of betamethasone or four doses of dexamethasone, which complete the course [ 11 ]. In these cases of imminent delivery, international guidelines recommend an administration of at least one dose of prenatal corticosteroid.…”
Section: Introductionmentioning
confidence: 99%
“…Taking corticosteroids between 34 to 36 weeks of gestation promotes fetal lung development, increases neonatal Apgar score, and reduces the likelihood of RDS [ 4 , 5 ]. Additionally, treatment with glucocorticoids in such pregnancies can reduce neonatal mortality and morbidity due to reducing the risk for intraventricular hemorrhage, necrotizing enterocolitis, decrease the need for intensive care unit cares, and increase the risk of sepsis in the first 48 h of neonatal life [ 6 8 ]. Human studies have also shown that betamethasone used during pregnancy can potentially affect placental function, fetal growth, hypothalamic-pituitary-adrenal axis development, and endocrine stress responses during infancy [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%